Maximizing the Work Environment - Saddam Ikhsan, Andy; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
Human (HR) is a part of organizational management that focuses on the human resource element. The task of human resource management is to manage the human element well in order to obtain a workforce that is satisfied with their work. In organizations, humans are one of the most important elements in an organization. This research aims to examine the influence of leadership style and role conflict on the work environment with communication as an intervening variable at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Leadership style has a positive and significant effect on communication with an original sample value of 0.219 and an ap value of 0.017. Leadership Style has a positive and significant effect on the Work Environment with an original sample value of 0.362 and ap value of 0.008. Communication has a positive and insignificant effect on the work environment with an original sample value of 0.224 and ap value of 0.065. Role Conflict has a positive and significant effect on the Work Environment with an original sample value of 0.680 and ap value of 0.000. Role Conflict has a positive and insignificant effect on the Work Environment with an original sample value of 0.273 and ap value of 0.053. Leadership Style has a positive and insignificant effect on the Work Environment through Communication with an original sample value of 0.049 and ap value of 0.124. Leadership Role Conflict has a positive and insignificant effect on the Work Environment through Communication with an original sample value of 0.049 and ap value of 0.124.